Réponses

2014-02-04T14:19:33+01:00
D = 2x² + 6x + x² - 3x - x² + 3x - 2x - 6x
D = 2x
² + x² - x² + 6x - 6x - 3x + 3x - 2x
D = 2x² - 2x

E = 9 - x² + 3x² - 9x + 7 + 5x
³ - 7x³
E = 5x³ - 7x³ - x² + 3x² - 9x + 7 + 9
E = -2x³ + 2x² - 9x + 16

F = 2x
³ + 4 - 6x² + x² - 2x + 9x - 3x -9x
F = 2x
³ - 6x² + x² - 2x + 9x - 9x - 3x + 4
F = 2x³ - 5x² - 5x + 4
2014-02-04T15:12:10+01:00
D = 2x²+6x+x²-3x-x²+3x-2x-6x
   = 2x²- 2x

E= 9-x²+3x²-9x+7+5x^3-7x^3
   = -2x³ + 2x² - 9x + 16

F=2x^3+4-6x²+x²-2x+9x-3x-9x
 = 2x³ - 5x² - 5x + 4